Host cell and antibody response towards Pasteurella multocida B2 infection-a general review - Lim, Eric Teik Chung; Abdullah, Faez Firdaus Jesse; Abba, Yusuf; Marza, Ali Dhiaa; Ibrahim, Hayder Hamzah; Saad, Mohd Zamri; Haron, Abd Wahid; Saharee, Abdul Aziz; Mohd Lila, Mohd Azmi (Science Publications, 2015)
Pasteurella multocida was first shown to be the causative agent of fowl cholera by Louis Pasteur in 1881. Since then, this Gramnegative bacterium has been identified as the causative agent of many other economically important diseases in a wide range of hosts. Haemorrhagic Septicaemia (HS) is a disease, caused by Pasteurella multocida serotypes B2 and E2 that causes acute, highly fatal septicaemia with high morbidity and mortality in cattle and more susceptible in buffaloes. In this review, we aim to determine the host cell and antibody response towards Pasteurella multicoda B2 infection causing Haemorrhagic septicaemia.